Edible Insect Larvae in Kaytetye: Their Nomenclature and Significance. Issue Volume 37:Issues 1(2017) (March 2017) - Turpin, Myfany; Si, Aung
Insects have traditionally constituted an important source of food in many cultures, but changes in dietary practices and other lifestyle traits are threatening the transmission of insect-related knowledge and vocabulary to younger generations of Indigenous Australians. This paper describes the rich cultural and culinary traditions surrounding an important insect group, namely a class of edible insect larvae consumed by a desert community in central Australia. Twenty-nine different edible insect larvae are named in the Kaytetye language, with the names encoding the identity of the host plant on which the larvae are found. We describe the complexities involved in the naming system, paying special attention to cultural and linguistic factors. The difficulties in the scientific identification of these ethnotaxa are discussed, as are the significance of our data to (1) questions of universal patterns in ethnoclassification and nomenclature and (2) the purported lack of binomially-labeled folk species in the languages of hunter-gatherer societies.